2019
DOI: 10.1016/j.jpaa.2019.02.018
|View full text |Cite
|
Sign up to set email alerts
|

A characterisation of Lie algebras amongst anti-commutative algebras

Abstract: Let K be an infinite field. We prove that if a variety of anticommutative K-algebras-not necessarily associative, where xx " 0 is an identity-is locally algebraically cartesian closed, then it must be a variety of Lie algebras over K. In particular, Lie K is the largest such. Thus, for a given variety of anti-commutative K-algebras, the Jacobi identity becomes equivalent to a categorical condition: it is an identity in V if and only if V is a subvariety of a locally algebraically cartesian closed variety of an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…(Actually, he proved it for Lie algebras over a commutative ring with unit.) In our article [19] we managed to find a partial converse to this theorem: we showed that the condition (LACC) characterises Lie algebras amongst K-algebras with an alternating multiplication (xx " 0). The result is a simple categorical description of the Jacobi identity.…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…(Actually, he proved it for Lie algebras over a commutative ring with unit.) In our article [19] we managed to find a partial converse to this theorem: we showed that the condition (LACC) characterises Lie algebras amongst K-algebras with an alternating multiplication (xx " 0). The result is a simple categorical description of the Jacobi identity.…”
Section: Introductionmentioning
confidence: 94%
“…In Section 2 we start by recalling some definitions and basic properties of varieties of non-associative algebras, with in particular an analysis of the objects B5X in this context. This leads to Theorem 2.8 which provides a summary of the main result of [19]. Section 3 is devoted to the commutative case.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations